THE IMPERATIVE OF ESTABLISHING KAMPUNG MODERASI BERAGAMA AS A STRATEGY FOR NEIGHBORHOOD-BASED COMMUNITY EMPOWERMENT - Sulisman, Alya Nurayu; Stiawati, Titi (KOMUNITAS, 2023)
Kampung Moderasi Beragama is a tangible implementation of the concept of religious moderation integrated into the social structure, aiming to implement values of tolerance, mutual respect, and raise awareness of the community towards a harmonious environment. The importance of forming a Kampung Moderasi Beragama can be seen in the aspect of empowering environmentally-based communities. .The establishment of the Kampung Moderasi Beragama is crucial because it can have a positive impact and a significant influence on how religious moderation can play a role as a strategy for community empowerment that is beneficial in community life.